Duplex stainless steel, steel sheet, and method for manufacturing the steel sheet
Patent Information
- Application Number
- JP2025058467
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
- Estimated Expiration
- 2045-03-31
Smart Images

Figure 2026165857000001 
Figure 2026165857000002 
Figure 2026165857000003
Abstract
Description
[Technical Field]
[0001] The present invention relates to a duplex stainless steel sheet with excellent surface properties, duplex stainless steel for obtaining such a sheet through hot and / or cold working, and a method for manufacturing the sheet. [Background technology]
[0002] Duplex stainless steel, composed of ferrite and austenite, exhibits excellent resistance to seawater and stress corrosion cracking, and generally also possesses high strength. Therefore, it is used in components for seawater condensers, heat exchangers, flue gas desulfurization systems, and various chemical plant equipment. However, since duplex stainless steel undergoes hot working processes such as hot rolling and hot extrusion during manufacturing, high hot workability is required.
[0003] For example, Patent Document 1 discloses a method for improving the hot workability of duplex stainless steel, which involves controlling the balance of Cr, Mo, and N content as indicators of pitting corrosion resistance, as well as controlling the balance of N, S, and B content to suppress embrittlement of the ferrite-austenite interface. In other words, it is believed that the cause of decreased hot workability is the occurrence of cracks at the ferrite-austenite interface (phase interface) and grain boundaries, and the propagation of these cracks; therefore, it is stated that the balance of N, S, and B content, which strengthen the phase interface and grain boundaries, should be controlled. [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] Japanese Patent Publication No. 2024-006717 [Overview of the Initiative] [Problems that the invention aims to solve]
[0005] Generally, stainless steel sheets that are not painted require excellent surface properties. In the manufacturing process of duplex stainless steel, cracks that occur during hot working, as described above, have a significant impact on the surface properties. On the other hand, even small cracks that do not progress to the large cracks that are problematic in hot forging affect the surface properties of the steel sheet. Therefore, there has been a demand for duplex stainless steel materials that can control cracking and have superior surface properties.
[0006] The present invention has been made in view of the above circumstances, and its object is to provide a duplex stainless steel sheet with excellent surface properties, duplex stainless steel for obtaining such a steel sheet through hot and / or cold working, and a method for manufacturing the steel sheet. [Means for solving the problem]
[0007] The present invention relates to a duplex stainless steel sheet having a rolled duplex structure in which ferrite phase particles are dispersed in a substrate consisting of an austenite phase, with the composition in mass% being: Cr: 15.0~19.0%, Ni: 2.0~7.0%, Mo: 1.6~5.0%, C: 0.001~0.200%, Si: 0.01~0.90%, Mn: 0.01~2.00%, P: 0.010~0.050%, S: 0.0001~0.0050%, Cu: 0.01~1.00%, Al The composition of the material includes 0.0003-0.0040% of P, 0.0003-0.0040% of Sn, 0.001-0.200% of N, 0.0005-0.0100% of O, with Nb being 0.05% or less, and the remainder being Fe and unavoidable impurities. The composition of the material is characterized in that, when the mass % of element M is [M], the formula satisfies 70 < ([P] × 5000 + [S] × 500 + [Sn] × 5300 + [O] × 2500) < 280.
[0008] These characteristics make it possible to produce a duplex stainless steel sheet with excellent surface properties.
[0009] In the above invention, in optical observation of the surface, the number density of surface defects is set to 14 defects / 100 m 2The following features may also be included. According to these features, a duplex stainless steel sheet with superior surface properties can be produced.
[0010] In the above invention, in the component composition, δ cal δ defined as =4.3×(1.3×[Si]+[Cr]+[Mo]+2.2×[Al]+[Nb]+0.3×[Sn])-3.9×(30×[C]+30×[N]+[Ni]+0.8×[Mn]+0.3×[Cu])-31.5 cal The characteristic may be that the value is in the range of 5 to 25. With such a characteristic, a duplex stainless steel sheet with superior surface properties can be obtained.
[0011] Furthermore, the present invention relates to a duplex stainless steel that is rolled to produce a sheet material, wherein the composition is, in mass%, Cr: 15.0~19.0%, Ni: 2.0~7.0%, Mo: 1.6~5.0%, C: 0.001~0.200%, Si: 0.01~0.90%, Mn: 0.01~2.00%, P: 0.010~0.050%, S: 0.0001~0.0050%, Cu: 0.01~1.00%, Al: 0.0003~0.0040%, Sn: 0.0003~0.0040%, N: 0.001~0.200%, The composition has a component composition consisting of O: 0.0005~0.0100%, Nb: 0.05% or less, with the remainder being Fe and unavoidable impurities, and the said component composition satisfies 70 < ([P] × 5000 + [S] × 500 + [Sn] × 5300 + [O] × 2500) < 280 when the mass % of element M is [M], and has a two-phase structure in which ferrite phase particles are dispersed in an austenite phase base, and in the shape of the ferrite phase particles in a cross section perpendicular to the casting direction, S1: area of the ferrite phase particle (mm 2 ), where L is the perimeter of the ferrite phase particle (mm), (circularity) = 4π × S1 / L 2 The characteristic feature is that the simple average of the circularity defined by is 0.10 or higher.
[0012] According to these characteristics, a duplex stainless steel sheet with excellent surface properties can be obtained.
[0013] In the invention described above, in the component composition, δ cal =4.3×(1.3×[Si]+[Cr]+[Mo]+2.2×[Al]+[Nb]+0.3×[Sn])-3.9×(30×[C]+30×[N]+[Ni]+0.8×[Mn]+0.3×[Cu])-31.5, δ defined by the formula cal may be in the range of 5 to 25. According to this feature, a duplex stainless steel sheet with more excellent surface properties can be obtained.
[0014] Furthermore, the present invention is a method for manufacturing a duplex stainless steel sheet having a rolled duplex structure in which ferrite phase particles are dispersed in a matrix composed of an austenite phase, the component composition comprising, in mass%, Cr: 15.0 to 19.0%, Ni: 2.0 to 7.0%, Mo: 1.6 to 5.0%, C: 0.001 to 0.200%, Si: 0.01 to 0.90%, Mn: 0.01 to 2.00%, P: 0.010 to 0.050%, S: 0.0001 to 0.0050%, Cu: 0.01 to 1.00%, Al: 0.0003 to 0.0040%, Sn: 0.0003 to 0.0040%, N: 0.001 to 0.200%, O: 0.0005 to 0.0100%, with Nb being 0.05% or less, the balance being Fe and unavoidable impurities, wherein the component composition satisfies 70<([P]×5000+[S]×500+[Sn]×5300+[O]×2500)<280, where [M] is the mass% of element M, and in the shape of the ferrite phase particles in the cross section perpendicular to the casting direction, S1: the area of the ferrite phase particles (mm 2 ), L: the perimeter of the ferrite phase particles (mm), and a slab made of steel having a duplex structure in which ferrite phase particles are dispersed in a matrix composed of an austenite phase, wherein the simple average of the circularity defined by (circularity)=4π×S1 / L 2 is 0.10 or more, is heated to a temperature between 1100°C and 1270°C and then rolled.
[0015] According to this feature, a duplex stainless steel sheet having excellent surface properties can be obtained.
[0016] In the invention described above, in optical observation of the surface, the number density of surface defects is 14 pieces / 100m2 The configuration may be as follows. According to such a feature, a duplex stainless steel sheet with more excellent surface properties can be obtained.
[0017] In the above invention, in the component composition, δ cal defined by δ=4.3×(1.3×[Si]+[Cr]+[Mo]+2.2×[Al]+[Nb]+0.3×[Sn])-3.9×(30×[C]+30×[N]+[Ni]+0.8×[Mn]+0.3×[Cu])-31.5 cal may be in the range of 5 to 25. According to such a feature, a duplex stainless steel sheet with more excellent surface properties can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] [Figure 1] This is a scatter diagram showing the relationship between the circularity of ferrite phase particles in the cross section of the slab before hot rolling and the number density of surface defects in the duplex stainless steel sheet. [Figure 2] This is a schematic diagram showing the relationship between the magnitude of the circularity of ferrite phase particles and cracks caused by rolling. [Figure 3] This is a scatter diagram showing the relationship between the PSSnO value and the circularity of ferrite phase particles. [Figure 4] This is a list table of the chemical components of the steels used in the production test. [Figure 5] This is a list table showing the results of the production test. DETAILED DESCRIPTION OF EMBODIMENTS FOR CARRYING OUT THE INVENTION
[0019] The inventors of the present application have conducted extensive and intensive studies in order to manufacture a duplex stainless steel sheet having excellent surface properties.
[0020] First, we investigated surface defects occurring in duplex stainless steel sheets. Specifically, we collected samples containing surface defects (cracks) and observed the microstructure of the cross-sections containing the surface defects using SEM and optical microscopes. As a result, we found that the cracks originated at the ferrite / austenite phase interface and propagated along the ferrite / austenite phase interface for a long distance. Furthermore, no non-metallic inclusions that could cause cracking were found in the defective areas. Based on these findings, we further diligently studied the relationship between the morphology of the ferrite / austenite phase interface and cracking.
[0021] We investigated the shape of ferrite phase particles in slabs before hot rolling. Samples were cut from duplex stainless steel slabs from multiple lots, and the cross-section perpendicular to the casting direction was used as the observation surface. The samples were embedded in resin, the observation surface was mirror-polished, and then electrolytic etching was performed in a 10% potassium hydroxide etchant to reveal the microstructure. The microstructure of the observation surface was then observed using an optical microscope. In observing the microstructure, we focused on the shape of the ferrite phase particles and measured the particle size area and perimeter of more than 100 ferrite phase particles using image analysis software. The degree of sphericity of the ferrite phase particles was then evaluated by calculating the circularity, which is defined by the following formula. Circularity = 4π × S1 / L 2 In the same formula, S1 represents the area of the ferrite phase particles (mm²). 2 ), where L is the perimeter of the particle (mm).
[0022] Figure 1 shows the relationship between the circularity of ferrite phase particles and the surface defect properties of duplex stainless steel sheets. Here, the circularity was measured for slabs from multiple lots before hot rolling, and the number density of surface defects was investigated in the sheets obtained after hot rolling. It was found that the greater the circularity, that is, the closer the shape of the ferrite phase particles was to a sphere, the fewer surface defects there were. In particular, by setting the circularity to 0.10 or higher, good surface properties with a small number of surface defects were obtained.
[0023] Figure 2 schematically shows the relationship between the circularity of ferrite phase particles and surface properties. As mentioned above, a key factor in obtaining good surface properties in duplex stainless steel is suppressing the propagation of cracks along the austenite / ferrite phase interface, which is unique to duplex stainless steel.
[0024] First, as shown in Figure (a), we will explain the case where the ferrite phase particles 12 in the austenite phase 11 substrate have a small circularity, that is, the ferrite phase particles 12 have a thin, elongated shape, in the slab 1 before hot rolling. As shown in Figure (b), when obtaining the steel sheet 2, if fine cracks occur during hot rolling, the cracks 15 propagate along the austenite / ferrite phase interface, becoming larger cracks 15 and deteriorating the surface properties.
[0025] In contrast, as shown in Figure (c), when the ferrite phase particles 12 have a large circularity in the slab 1 before hot rolling, that is, when the ferrite phase particles 12 have a shape close to a sphere, as shown in Figure (d), even if fine cracks 15 occur during hot rolling, these cracks 15 are not allowed to propagate, and excellent surface properties can be obtained.
[0026] Cracks that occur in the steel sheet 2 after hot rolling can be removed by grinding if they are near the surface. While this may ensure good surface properties, it can also reduce yield and increase process load. Furthermore, if the circularity of the ferrite phase particles 12 is small before hot rolling, even if surface cracks are removed with a grinder after hot rolling, cracks may reappear on the surface during subsequent cold rolling. As shown in the figure, when the circularity of the ferrite phase particles 12 is small, cracks along the austenite / ferrite phase interface also exist inside the steel sheet. These cracks can propagate during cold rolling and appear as surface cracks.
[0027] Next, the inventors determined the relationship between each component of duplex stainless steel and the circularity according to the above formula by organizing a large amount of data.
[0028] As a result, as shown in Figure 3, it was found that there is a relationship between the values calculated from the content of P, S, Sn, and O and the circularity of the ferrite phase particles. In particular, it was concluded that duplex stainless steel with good surface properties can be obtained by controlling the "PSSnO value" for the content of these elements to a range of over 70 to less than 280. PSSnO value = ([P] × 5000 + [S] × 500 + [Sn] × 5300 + [O] × 2500) Note that [M] represents the mass percentage of element M in the composition of the steel. In other words, each element symbol is substituted with the mass percentage of the corresponding element.
[0029] The mechanism by which ferrite phase particles became spherical (increased circularity in cross-section) in the component composition satisfying the above-mentioned PSSnO value between 70 and less than 280 remains largely unknown. However, it is thought that the surface-activating elements S, Sn, and O act on the ferrite / austenite phase interface to promote the spheroidization of ferrite phase particles. Furthermore, it is thought that P, which has the effect of lowering the melting point, suppresses the formation of a network by bonding between ferrites by forming a residual liquid phase during solidification.
[0030] As described above, it was found that by precisely controlling the content of P, S, Sn, and O, and controlling the PSSnO value to be between 70 and 280, the ferrite phase particles can be spheroidized and surface defects can be suppressed.
[0031] Therefore, in this embodiment, a component composition was determined that includes, by mass%, Cr: 15.0~19.0%, Ni: 2.0~7.0%, Mo: 1.6~5.0%, C: 0.001~0.200%, Si: 0.01~0.90%, Mn: 0.01~2.00%, P: 0.010~0.050%, S: 0.0001~0.0050%, Cu: 0.01~1.00%, Al: 0.0003~0.0040%, Sn: 0.0003~0.0040%, N: 0.001~0.200%, O: 0.0005~0.0100%, with Nb: 0.05% or less. Furthermore, this component composition sets the PSSnO value to be in the range of greater than 70 to less than 280. Furthermore, the duplex stainless steel sheet in this embodiment has the component composition described above and has a rolled duplex structure in which ferrite phase particles are dispersed in a substrate consisting of an austenite phase. This makes it possible to produce a duplex stainless steel sheet with excellent surface properties.
[0032] Furthermore, it is preferable that the shape of the ferrite phase particles in the slab before hot rolling, in a cross-section perpendicular to the casting direction, has a simple average circularity of 0.10 or higher. Having such a microstructure in the slab allows for the suppression of crack propagation during hot rolling, as described above, and enables the creation of a duplex stainless steel sheet with excellent surface properties.
[0033] Furthermore, in the above-mentioned component composition, δ is defined by the following formula. cal It is also preferable to set it in the range of 5 to 25. δ cal The value of is a formula corresponding to the volume fraction of the ferrite phase in duplex stainless steel. And δ cal A small value of results in a lower volume fraction of the ferrite phase, leading to an increase in segregated elements such as P and S at the grain boundaries during solidification, making cracking more likely during hot rolling. On the other hand, δ cal A large value of δ increases the volume proportion of the ferrite phase, which increases the area proportion of the ferrite / austenite phase interface that serves as the initiation point for cracks during hot rolling, and thus increases the surface defects in the resulting duplex stainless steel material. calIt is preferable to keep the value of within the range described above. In the same formula, [M] is the mass % of the content of element M in the composition of the steel. δ cal =4.3×(1.3×[Si]+[Cr]+[Mo]+2.2×[Al]+[Nb]+0.3×[Sn])-3.9×(30×[C]+30×[N]+[Ni]+0.8×[Mn]+0.3×[Cu])-31.5
[0034] Furthermore, in the obtained duplex stainless steel sheet, the number density of surface defects was found to be 14 defects / 100m² by optical observation of the surface. 2 The following is also preferable. Details of the method for measuring the number density of surface defects will be described later.
[0035] <Manufacturing Test> Next, we will explain the results of manufacturing duplex stainless steel sheets by producing slabs with multiple component compositions shown in Figure 4 using the following manufacturing method, and then hot-rolling those slabs under the conditions shown in Figure 5.
[0036] First, raw materials such as stainless steel scrap were melted in a 60-ton electric furnace. Then, oxygen blowing (oxidative refining) was performed in the electric furnace and an AOD (argon-oxygen smelting furnace) to remove unwanted carbon. Limestone and fluorite were then added to produce a CaO-SiO2-AlO3-MgO-F slag. Furthermore, pure Si and / or Al were added to deoxidize by Cr reduction, and then Ar was stirred to desulfurize. After that, the molten metal was poured into a ladle, the temperature was adjusted, and the components such as P, S, and Sn were adjusted. Finally, 150 mm thick slabs were produced by continuous casting. Samples for component analysis were taken from the tundish during continuous casting.
[0037] Here, P, S, Sn, and O have a significant effect on the circularity of ferrite phase particles in the slab before hot rolling, so their content is precisely controlled. In order to precisely control the trace amounts of P, S, and Sn, we first investigated the raw materials. As a result, we found that the main source of P contamination was deposits on the inner surface of pipe-shaped scrap in the raw materials. We also found that the main source of S contamination was scrap of S-containing steel, such as free-cutting steel. Furthermore, we found that the main source of Sn contamination was specific scrap, such as scrap with plating attached. Therefore, we sorted the scrap used as raw materials to prevent the unexpected contamination of P, S, and Sn.
[0038] Furthermore, if the phosphorus (P) concentration is low during the refining process in steelmaking, an Fe-20wt%P alloy is added to prevent evaporation loss and distribution loss of P to the slag, making it possible to precisely control the P content.
[0039] Furthermore, regarding sulfur (S), the S content was precisely controlled by removing S using slag with a composition where the mass ratio of CaO to SiO2 during the refining process was 1.5 to 22. In this type of slag-based S removal, the concentration of O in the molten metal is important as well as the slag composition, resulting in precise control of the O content. The S content can also be precisely controlled by controlling the concentrations of deoxidizing agents Al, Si, and Mn in the molten metal. If the S concentration is low during the refining process in steelmaking, the addition of Fe-25wt%S alloy prevents distribution loss to the slag during S addition, making it possible to precisely control the S content.
[0040] Furthermore, if the Sn concentration is low during the refining process in steelmaking, a Ni-40wt%Sn alloy can be added to prevent Sn evaporation loss and enable precise control of the Sn content.
[0041] Samples were taken from the obtained slabs to measure the circularity of the ferrite phase particles. Each slab was then heated at the temperature and heating time specified above and hot-rolled to form steel plates of the thickness shown in the figure (3.0 to 6.0 mm). Subsequently, the steel plates were annealed and pickled to remove surface scale. Further cold rolling was performed to form duplex stainless steel plates with a width of 1 m and a thickness of 1 mm. The duplex stainless steel plates were manufactured in coil form. In this way, duplex stainless steel plates having a rolled duplex structure in which ferrite phase particles are dispersed in an austenite phase substrate can be obtained.
[0042] The conditions for hot rolling are determined as follows: Duplex stainless steel slabs cast in a continuous casting machine are heated in a heating furnace before hot rolling. If the heating temperature is too low, the ductility during hot rolling will be insufficient, causing cracks on the surface. If the heating temperature is too high, segregation of segregating elements such as P and S generated during solidification in continuous casting will occur at the grain boundaries, exceeding the ductility recovery temperature (Nil temperature: the temperature at which embrittlement occurs as the temperature is increased), resulting in poor ductility and the generation of brittle cracks at the grain boundaries, deteriorating the surface properties. Furthermore, if the heating time before hot rolling is too short, the temperature of the entire slab will be uneven, with the center being at a lower temperature, causing cracks on the surface and inside due to uneven ductility in the thickness direction during hot rolling. If the heating time is too long, a thick scale will form on the slab surface, and even if water spraying is performed to remove the scale during hot rolling, the scale will remain, leading to fine cracks and deteriorating the surface properties. Cracks will also occur at the interface between the scale and the duplex stainless steel. Therefore, it is preferable that the heating temperature before hot rolling be 1100°C to 1270°C and the heating time be 2.0 to 8.0 hours. More preferably, the heating temperature before hot rolling be 1150°C to 1250°C and the heating time be 3.0 to 6.0 hours.
[0043] The chemical composition of the duplex stainless steel was determined by quantitative analysis using a fluorescence X-ray analyzer with the sample used for the component analysis described above. The oxygen content was determined by quantitative analysis using inert gas impulse fusion infrared absorption spectroscopy.
[0044] The circularity of the ferrite phase particles was determined as follows: A specimen was prepared so that the observation surface was perpendicular to the longitudinal direction, which is the casting direction of the slab before hot rolling. The sampling location and size of the specimen are not particularly limited. The observation surface of the prepared specimen was mirror-polished. The mirror-polished observation surface was electrolytically etched in a 10% potassium hydroxide etchant to reveal the microstructure. The observation surface with the revealed microstructure was observed in 10 fields of view using an optical microscope. The measurement field of view is not particularly limited, but here it was 1.00 mm. 2 The area was observed at a magnification of 100x. In each field of view, the ferrite phase was identified from the contrast, and for each identified ferrite phase particle, the particle area and perimeter were measured, and the circularity of each particle was calculated. The circularity was measured for a total of 100 or more particles across 10 fields of view, and the simple average was calculated and recorded. Image analysis software was used to measure the particle area and perimeter.
[0045] For surface defects, the surface of the duplex stainless steel sheet was visually observed using optical inspection, and the number of surface defects caused by cracks during cold or hot working was measured. The measurement range was the entire surface of the coil, which was 1 m wide and 100 m long. If the number of surface defects in the measurement range was 1 or less, it was evaluated as best ("◎"), if it was 2 to 5, it was evaluated as good ("〇"), if it was 6 to 9, it was evaluated as good ("△"), if it was 10 to 14, it was evaluated as acceptable ("□"), and if it was 15 or more, it was evaluated as unacceptable ("×"). The measurement range was 100 m. 2 Therefore, if we consider the number of surface defects in this measurement range to be 1, the number density is 1 defect / 100m 2 That is the case.
[0046] As shown in Figure 5, the duplex stainless steel sheets obtained in Examples 1 to 18 all received a surface defect evaluation of "acceptable" or higher, indicating that relatively good surface properties were obtained. Of these, Examples 1 to 7 achieved particularly good surface properties, with a surface defect evaluation of "excellent" or higher.
[0047] Referring again to Figure 4, Examples 8, 9, and 12 had relatively high P, S, Sn, and O content, and although the PSSnO values were in the range of over 70 to less than 280, they were relatively large at 256, 242, and 275. As a result, the circularity of the ferrite phase particles was relatively low, and cracks were observed at the ferrite / austenite phase interface, which are thought to have occurred during hot rolling and cold rolling, resulting in a surface defect evaluation of "good".
[0048] In Examples 10 and 11, the P, S, Sn, and O content was relatively low, and although the PSSnO value was in the range of over 70 to less than 280, it was relatively small at 70 and 75. As a result, the circularity of the ferrite phase particles was relatively low, and cracks were observed at the ferrite / austenite phase interface, which are thought to have occurred during hot rolling and cold rolling, resulting in a surface defect evaluation of "good".
[0049] Regarding Example 13, δ cal The value was a large 29. This suggests that the volume fraction of the ferrite phase increased, leading to an increased area proportion of the ferrite / austenite phase interface, which serves as the starting point for cracking. As a result, cracking was observed at the ferrite / austenite phase interface, and the surface defect evaluation was rated as "acceptable".
[0050] Regarding Example 14, δ cal The value was small, at 3. This suggests that the volume fraction of the ferrite phase was low, leading to an increase in segregated elements such as P and S at the grain boundaries during solidification, making it easier for fine cracks to occur during hot rolling. As a result, the surface defect evaluation was rated as "acceptable".
[0051] In Example 15, the heating temperature before hot rolling was relatively high at 1280°C. Therefore, it is thought that the segregation of grain boundaries that occurred during solidification in continuous casting exceeded the nil temperature, resulting in insufficient ductility and the formation of brittle cracks at the grain boundaries. As a result, the evaluation of surface defects was rated as "acceptable".
[0052] In Example 16, the heating temperature before hot rolling was relatively low at 1080°C. Therefore, it is thought that insufficient ductility during hot rolling caused cracks to form on the surface, and that cracks were more likely to occur at the ferrite / austenite phase interface during both hot and cold rolling. As a result, the surface defect evaluation was rated as "acceptable".
[0053] In Example 17, the heating time before hot rolling was relatively short at 1.8 hours. Therefore, it was insufficient for soaking the slab, and it is thought that the hot rolling was performed with the center of the slab remaining at a low temperature, sometimes causing cracks on the surface and inside due to uneven ductility in the thickness direction. As a result, the evaluation of surface defects was given as "acceptable".
[0054] In Example 18, the heating time before hot rolling was relatively long at 8.3 hours. As a result, a thick layer of scale formed on the slab surface, and even after water spraying to remove the scale during hot rolling, the scale remained. This is thought to have worsened the surface properties, accompanied by fine cracks. Consequently, the evaluation of surface defects was rated as "acceptable".
[0055] On the other hand, Comparative Examples 1 to 8 all resulted in a "failure" evaluation of surface defects. Each example will be explained below.
[0056] In Comparative Example 1, although the individual contents of P, S, Sn, and O were not particularly high, the overall content was high, resulting in a large PSSnO value of 287. Furthermore, the circularity of the ferrite phase particles in the slab before hot rolling was reduced to 0.07. It is believed that cracking occurred frequently at the ferrite / austenite phase interface during hot and cold rolling. As a result, the evaluation of surface defects was deemed "unacceptable".
[0057] In Comparative Example 2, although the individual contents of P, S, Sn, and O were not particularly low, the overall content was low, resulting in a small PSSnO value of 55. Furthermore, the circularity of the ferrite phase particles in the slab before hot rolling was reduced to 0.05. It is thought that cracking occurred frequently at the ferrite / austenite phase interface during hot and cold rolling. As a result, the evaluation of surface defects was deemed "unacceptable".
[0058] In Comparative Examples 3 and 4, the individual content of two of the elements P, S, Sn, and O was particularly low, resulting in low PSSnO values of 43 and 57, respectively. Furthermore, the circularity of the ferrite phase particles in the slab before hot rolling was reduced to 0.02 and 0.05, respectively. It is believed that cracking occurred frequently at the ferrite / austenite phase interface during hot and cold rolling. As a result, the evaluation of surface defects was deemed "unacceptable."
[0059] In Comparative Examples 5 and 6, the individual content of P, S, Sn, and O was particularly high in one and two elements, respectively, resulting in high PSSnO values of 305 and 302, and further reducing the circularity of the ferrite phase particles in the slabs before hot rolling to 0.04 and 0.06, respectively. It is believed that cracking occurred frequently at the ferrite / austenite phase interface during hot and cold rolling. As a result, the evaluation of surface defects was deemed "unacceptable".
[0060] In Comparative Example 7, the content of P, S, and Sn was relatively high, and the content of O was particularly high, resulting in a large PSSnO value of 304. Furthermore, the circularity of the ferrite phase particles in the slab before hot rolling was reduced to 0.04. It is thought that cracking occurred frequently at the ferrite / austenite phase interface during hot and cold rolling. Also, δ cal The value of [the other value] was also large. In particular, the high O content resulted in surface defects caused by nonmetallic inclusions. As a result, the evaluation of surface defects was deemed "unacceptable".
[0061] In Comparative Example 8, the individual content of P, S, Sn, and O was all high, resulting in a large PSSnO value of 332. Furthermore, the circularity of the ferrite phase particles in the slab before hot rolling was reduced to 0.01. It is thought that this led to frequent cracking at the ferrite / austenite phase interface during both hot and cold rolling. cal The value was also small. As a result, the evaluation of surface defects was deemed "unacceptable".
[0062] As described above, duplex stainless steel sheets with excellent surface properties could be manufactured using the steels of Examples 1 to 18.
[0063] By the way, the range of the component composition of the steel of the present invention, including Examples 1 to 18, is defined as follows.
[0064] Carbon (C) is necessary to ensure the mechanical strength of the resulting duplex stainless steel sheet. However, excessive C content can lead to the precipitation of carbides such as Cr carbides, causing embrittlement. Considering these factors, the amount of C is within the range of 0.001 to 0.200% by mass, preferably within the range of 0.005 to 0.150%, and more preferably within the range of 0.010 to 0.120%.
[0065] Si is an effective element for deoxidation and is necessary to obtain a sufficient deoxidation effect. On the other hand, if included in excess, it can form a σ phase, reduce corrosion resistance, and cause embrittlement. Taking these factors into consideration, the amount of Si is in the range of 0.01 to 0.90% by mass, preferably in the range of 0.10 to 0.80%, and more preferably in the range of 0.20 to 0.70%.
[0066] Mn is a useful and necessary element for deoxidation. On the other hand, excessive amounts of Mn can reduce corrosion resistance. Taking these factors into consideration, the amount of Mn is in the range of 0.01 to 2.00% by mass, preferably in the range of 0.10 to 1.50%, and more preferably in the range of 0.20 to 1.20%.
[0067] P has the effect of lowering the melting point of steel and, by forming a residual liquid phase during solidification, suppresses the network-like connections of the ferrite phase, which is useful for homogenizing and spheroidizing ferrite phase particles, making it one of the important elements. On the other hand, if included in excess, it segregates at the grain boundaries, worsening hot workability and causing cracking during hot rolling. Taking these factors into consideration, the amount of P is in the range of 0.010 to 0.050% by mass, preferably in the range of 0.012 to 0.040%, and more preferably in the range of 0.015 to 0.038%.
[0068] S is an interfacial activating element and is one of the important elements that acts on the ferrite / austenite phase interface to spheroidize ferrite phase particles. On the other hand, if included in excess, it segregates at the grain boundaries, worsening hot workability and causing cracking during hot rolling. Taking these factors into consideration, the amount of S is in the range of 0.0001 to 0.0050% by mass, preferably in the range of 0.0002 to 0.0040%, and more preferably in the range of 0.0003 to 0.0030%.
[0069] Ni is necessary to ensure the toughness of the resulting duplex stainless steel sheet. However, excessive amounts increase the cost of the material. Taking these factors into consideration, the amount of Ni is in the range of 2.0 to 7.0% by mass, preferably in the range of 3.0 to 6.5%, and more preferably in the range of 3.5 to 6.0%.
[0070] Cr is essential for maintaining corrosion resistance by forming a dense passive film on the surface of duplex stainless steel sheets. On the other hand, excessive amounts of Cr form carbides, which reduces corrosion resistance. Taking these factors into consideration, the amount of Cr is 15.0 to 19.0% by mass, preferably 15.5 to 18.0%, and more preferably 16.0 to 17.0%.
[0071] Mo has the effect of improving corrosion resistance and its inclusion is necessary. On the other hand, excessive inclusion increases the cost of the material. Taking these factors into consideration, the amount of Mo is in the range of 1.6 to 5.0% by mass, preferably in the range of 1.8 to 4.5%, and more preferably in the range of 2.0 to 4.0%.
[0072] Cu is required to ensure the toughness of the resulting duplex stainless steel sheet. However, excessive amounts can form carbides, negatively affecting corrosion resistance. Considering these factors, the amount of Cu is in the range of 0.01 to 1.00% by mass, preferably in the range of 0.02 to 0.50%, and more preferably in the range of 0.03 to 0.30%.
[0073] Al is required as a deoxidizing element, particularly reducing the number of oxide inclusions that cause surface defects. On the other hand, if included in excess, it reduces MgO bricks used in refractories in the steelmaking process, such as ladles, increasing the Mg concentration in the molten metal and generating nonmetallic inclusions mainly composed of MgO·Al2O3, which tend to coarseen, thus adversely affecting the surface properties. Taking these factors into consideration, the amount of Al is in the range of 0.0003 to 0.0040% by mass, preferably in the range of 0.0005 to 0.0035%, and more preferably in the range of 0.0010 to 0.0030%.
[0074] Since excessive Nb content can lead to the formation of carbides and cause embrittlement, it is desirable to reduce its content as much as possible. Therefore, the Nb content is set to 0.05% or less by mass, preferably 0.04% or less, and more preferably 0.03% or less.
[0075] Sn is an interfacial activating element that acts on the ferrite / austenite phase interface to spheroidize ferrite phase particles. Therefore, although present in trace amounts, it is an important element that needs to be precisely controlled. On the other hand, excessive amounts of Sn can segregate at grain boundaries, worsening hot workability and causing cracking during hot rolling. Considering these factors, the amount of Sn is in the range of 0.0003 to 0.0040% by mass, preferably in the range of 0.0005 to 0.0028%, and more preferably in the range of 0.0010 to 0.0023%.
[0076] Nitrogen (N) is necessary to ensure the mechanical strength of the resulting duplex stainless steel sheet. However, excessive amounts of N form Cr nitrides, which negatively affect corrosion resistance. Considering these factors, the amount of N is in the range of 0.001 to 0.200% by mass, preferably in the range of 0.005 to 0.150%, and more preferably in the range of 0.010 to 0.120%.
[0077] O is an interfacial activating element and is one of the important elements that acts on the ferrite / austenite phase interface to spheroidize ferrite phase particles. On the other hand, if included in excess, it increases the number of nonmetallic inclusions that cause surface defects. As mentioned above, controlling the O concentration in molten steel also controls the desulfurization process during the refining stage, which is necessary for precise control of the S concentration. Taking these factors into consideration, the O concentration is in the range of 0.0005 to 0.0100% by mass, preferably in the range of 0.0010 to 0.0090%, and more preferably in the range of 0.0020 to 0.0080%.
[0078] The PSSnO value is an indicator for sufficiently spheroidizing ferrite phase particles. Although many aspects of the mechanism for spheroidizing ferrite phase particles are unclear, the surface-activating elements S, Sn, and O act on the ferrite / austenite phase interface to promote spheroidization of ferrite phase particles. Furthermore, P, which has the effect of lowering the melting point, is thought to contribute to the spheroidization of ferrite phase particles by suppressing the formation of a network due to bonding between ferrites by forming a residual liquid phase during solidification. On the other hand, if S, Sn, and O are present in excess, the energy of the ferrite / austenite phase interface is lowered too much, which can actually cause coarsening of the ferrite phase particles. Also, if P is present in excess, the amount of residual liquid phase during solidification is excessive, which is thought to lead to non-uniformity of the structure. Taking these factors into consideration, the PSSnO value is set in the range of greater than 70 to less than 280, preferably in the range of greater than 80 to less than 240, and more preferably in the range of greater than 100 to less than 170.
[0079] δ cal The value of δ is an indicator of the volume fraction of the ferrite phase in duplex stainless steel. cal If the value of is small, it lowers the volume fraction of the ferrite phase, increasing the segregation of segregating elements such as P and S at the grain boundaries during solidification, making it easier for cracks to occur during hot rolling. On the other hand, δ cal A larger value of increases the volume fraction of the ferrite phase, increases the area ratio occupied by the ferrite / austenite phase interface which is the starting point for cracking, and increases surface defects. Considering these factors, δ cal The value of is preferably in the range of 5 to 25, more preferably in the range of 8 to 23, and even more preferably in the range of 10 to 20.
[0080] Although representative embodiments of the present invention and modifications thereof have been described above, the present invention is not necessarily limited thereto, and those skilled in the art will be able to find various alternative embodiments and modifications without departing from the spirit of the present invention or the scope of the attached claims.
Claims
1. A duplex stainless steel sheet having a rolled duplex structure in which ferrite phase particles are dispersed in a substrate consisting of an austenite phase, In mass percent, Cr: 15.0-19.0%, Ni: 2.0 to 7.0%, Mo: 1.6-5.0%, C: 0.001-0.200%, Si: 0.01-0.90%, Mn: 0.01 to 2.00%, P: 0.010-0.050%, S: 0.0001 to 0.0050%, Cu: 0.01 to 1.00%, Al: 0.0003 to 0.0040%, Sn: 0.0003 to 0.0040%, N: 0.001-0.200%, O: 0.0005-0.0100%, Includes, The composition has Nb: 0.05% or less, with the remainder being Fe and unavoidable impurities. The above component composition is such that when the mass percentage of element M is [M], 70<([P]×5000+[S]×500+[Sn]×5300+[O]×2500)<280 A duplex stainless steel sheet characterized by satisfying the following conditions.
2. In optical observation of the surface, the number density of surface defects is 14 defects / 100 m 2 The duplex stainless steel sheet according to claim 1, characterized in that it is as follows:
3. In the above component composition, δ cal =4.3×(1.3×[Si]+[Cr]+[Mo] +2.2×[Al]+[Nb]+0.3×[Sn]) -3.9×(30×[C]+30×[N]+[Ni] +0.8×[Mn]+0.3×[Cu])-31.5 δ defined by cal A duplex stainless steel sheet according to claim 1 or 2, characterized in that the range is 5 to 25.
4. Duplex stainless steel that is rolled to give sheet material, In mass percent, Cr: 15.0-19.0%, Ni: 2.0 to 7.0%, Mo: 1.6-5.0%, C: 0.001-0.200%, Si: 0.01-0.90%, Mn: 0.01 to 2.00%, P: 0.010-0.050%, S: 0.0001 to 0.0050%, Cu: 0.01 to 1.00%, Al: 0.0003 to 0.0040%, Sn: 0.0003 to 0.0040%, N: 0.001-0.200%, O: 0.0005-0.0100%, Includes, The composition has Nb: 0.05% or less, with the remainder being Fe and unavoidable impurities. The above component composition is such that when the mass percentage of element M is [M], 70<([P]×5000+[S]×500+[Sn]×5300+[O]×2500)<280 Satisfying the conditions, It has a two-phase structure in which ferrite phase particles are dispersed in a substrate consisting of an austenite phase. In the shape of the ferrite phase particles in a cross-section perpendicular to the longitudinal direction, S 1 Area of ferrite phase particles (mm²) 2 ), where L is the perimeter of the ferrite phase particle (mm), and (circularity) = 4π × S 1 / L 2 A duplex stainless steel characterized by having a simple average of circularity defined by 0.10 or higher.
5. In the above component composition, δ cal =4.3×(1.3×[Si]+[Cr]+[Mo] +2.2×[Al]+[Nb]+0.3×[Sn]) -3.9×(30×[C]+30×[N]+[Ni] +0.8×[Mn]+0.3×[Cu])-31.5 δ defined by cal is in the range of 5 to 25, the duplex stainless steel according to claim 4.
6. A method for manufacturing a duplex stainless steel sheet having a rolled duplex structure in which ferrite phase particles are dispersed in a substrate consisting of an austenite phase, In mass percent, Cr: 15.0-19.0%, Ni: 2.0 to 7.0%, Mo: 1.6-5.0%, C: 0.001-0.200%, Si: 0.01-0.90%, Mn: 0.01 to 2.00%, P: 0.010-0.050%, S: 0.0001 to 0.0050%, Cu: 0.01 to 1.00%, Al: 0.0003 to 0.0040%, Sn: 0.0003 to 0.0040%, N: 0.001-0.200%, O: 0.0005-0.0100%, Includes, The composition has Nb: 0.05% or less, with the remainder being Fe and unavoidable impurities. The above component composition is such that when the mass percentage of element M is [M], 70<([P]×5000+[S]×500+[Sn]×5300+[O]×2500)<280 Satisfying the conditions, In the shape of ferrite phase particles in a cross-section perpendicular to the casting direction, S 1 Area of ferrite phase particles (mm²) 2 ), where L is the perimeter of the ferrite phase particle (mm), and (circularity) = 4π × S 1 / L 2 A method for manufacturing a duplex stainless steel sheet, characterized by heating and rolling a slab made of steel having a duplex structure in which ferrite phase particles are dispersed in a base material consisting of an austenite phase having a simple average of circularity defined as 0.10 or more to a temperature between 1100°C and 1270°C.
7. In optical observation of the surface, the number density of surface defects is 14 defects / 100 m 2 The method for manufacturing a duplex stainless steel sheet according to claim 6, characterized in that it is as follows:
8. In the above component composition, δ cal =4.3×(1.3×[Si]+[Cr]+[Mo] +2.2×[Al]+[Nb]+0.3×[Sn]) -3.9×(30×[C]+30×[N]+[Ni] +0.8×[Mn]+0.3×[Cu])-31.5 δ defined by cal A method for manufacturing a duplex stainless steel sheet according to claim 6 or 7, characterized in that the range is 5 to 25.
Citation Information
Patent Citations
Duplex stainless steel material
JP2024006717A